Statistical Analysis of Badminton Three-Zone Lunge: Training versus Singles - Lee, J. J. J.; Loh, W. P. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Proper footwork with good lunge motion skills is an important element for high performance in badminton. Various researchers reported on the kinematic parameters to optimize lunge performance. However, there is a limited study on the difference in lunge performance during training and in singles. This research aims to study the lunge motion between the university and national level players in training compared to singles at three-zone lunge: Left-Forward (LF), CenterForward (CF), and Right-Forward (RF). Video captures of experiments between six university-level players and a Malaysian national-level player on lunge training and singles simulation were considered. The badminton performance metrics were the step forward and perform time of lunging. The paired sample t-test and one-way Analysis of Variance (ANOVA) statistical analysis were used to evaluate the withingroup (comparing same players’ level) and the between-group approach (comparing different players’ level) on 95% confidence level (p<0.05). Findings showed that the university players’ lunge training has no effect in the singles at RF zone, while the national players showed more consistent performances in three-zone lunges during training; as good as it does in the singles.